2006
DOI: 10.1097/01.wnr.0000221833.41340.cd
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of ATP-binding cassette subfamily-A transporter gene expression in primary human brain cells

Abstract: Five ATP-binding cassette (ABC) subfamily-A transporters (ABCA1, ABCA2, ABCA3, ABCA7 and ABCA8) are expressed in the brain. These transporters may regulate brain lipid transport; however, their relative expression level in isolated human brain cells is unknown. We developed real-time polymerase chain reaction assays to quantify the expression of these genes in human neurons, astrocytes, oligodendrocytes, microglia and cell lines. Neurons expressed predominantly ABCA1 and ABCA3; astrocytes ABCA1, ABCA2 and ABCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 25 publications
1
106
0
4
Order By: Relevance
“…ABCA transporters (ABCA1-13) have been shown to regulate lipid transport and gene expression data highlights that human astrocytes express ABCA1-3 at the mRNA level (220). There is however contrasting evidence at the protein level (221,222).…”
Section: Atp-binding Cassette Transporter Familymentioning
confidence: 99%
See 1 more Smart Citation
“…ABCA transporters (ABCA1-13) have been shown to regulate lipid transport and gene expression data highlights that human astrocytes express ABCA1-3 at the mRNA level (220). There is however contrasting evidence at the protein level (221,222).…”
Section: Atp-binding Cassette Transporter Familymentioning
confidence: 99%
“…For example, ABCA7 has been strongly implicated in APP processing, Aβ generation and the onset of dementia (224,225). However, the individual cellular role(s) of ABCA7 remains unresolved, and this is key given its widespread distribution (220,225). This shortfall in our understanding currently limits a critical appraisal of the role these astrocytic transporters may play in revealing a novel strategy to better manage AD pathology.…”
Section: Atp-binding Cassette Transporter Familymentioning
confidence: 99%
“…A recent real-time reverse transcription-polymerase chain reaction (RT-PCR) assay has been used to investigate the specific expression pattern of the ABC subfamily-A transporters in the brain and has shown that neurons express predominantly ABCA1 and ABCA3; astrocytes express ABCA1, ABCA2 and ABCA3; microglia express ABCA1 and oligodendrocytes express ABCA2 and ABCA3 [105]. With its expression in liver and brain, ABCB1 -the prototype of the B subclass of transporters -and ABCA1 regulate the high-density lipoprotein levels in the plasma and cholesterol contents of several cell types in these organs [106][107][108][109][110][111][112][113][114].…”
Section: Abc Transporters In the Brainmentioning
confidence: 99%
“…ABCA7 is highly expressed in brain tissue,9, 21, 22 most abundant in microglia and oligodendrocytes 7, 23. Previous studies comparing ABCA7 knock‐out mice with wild‐type mice or J20 amyloidogenic mice demonstrate that ABCA7 is involved in clearance of amyloid‐ β in the brain through phagocytosis 12, 24.…”
Section: Introductionmentioning
confidence: 99%